The Role of Reason in Structuring Islamic Spirituality as a Framework for the Formation of Faith According to the Qur’an and the Sunnah - Wahidah Wahidah; Mahyuddin Barni; Abdul Basir; Ali Muammar (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to examine the role of reason in framing Islamic spirituality as a foundation of faith according to the perspectives of the Qur’an and the Sunnah. In Islamic tradition, reason holds a significant position as a human instrument for understanding the signs of divinity, interpreting revealed teachings, and developing a strong and well-directed spiritual consciousness. This research employs a literature review method by examining primary sources such as the Qur’an, authentic hadiths, and the works of both classical and contemporary scholars who discuss the relationship between reason, spirituality, and faith. The findings indicate that reason is not merely a rational tool but also a means of perfecting faith by strengthening conviction through reflection, contemplation, and internalization of the principles of monotheism. The study reveals that reason and spirituality are not two opposing poles; rather, they are complementary aspects that together construct a comprehensive framework of faith. Accordingly, this research affirms that the integration of reason and spirituality constitutes the core of establishing strong faith in Islam, as demonstrated in various Qur’anic verses and prophetic traditions. Overall, this article is expected to offer a theoretical contribution to understanding the construction of Islamic faith that balances rational and spiritual dimensions, and to serve as a reference for Islamic studies that adopt an integrative approach between revelation and intellect